Efektivitas Penyelenggaraan Klaim Jaminan Kematian BPJS Ketenagakerjan Atas Kematian Pekerja Migran Indonesia Di Jawa Timur - Kiki Meylia Darma Esicho; Wiwin Yulianingsih (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Work is the primary need of every human being. By working, they will get a salary or wages that becomes the exchange rate to buy various necessities for life. But unfortunately, the fact is that getting a job in Indonesia is not an easy thing. This encourages people, especially those with education from elementary school to high school, to look for job opportunities abroad. From an economic perspective, the rapidly growing world market and the influence of globalization have opened up demand for workers in foreign economic sectors. Migrant workers act as accomplices and agents of economic and social progress in their country of origin and their country of placement. However, they are also very vulnerable to risks that can result in death. In this regard, the state is responsible for providing proper welfare for its citizens by providing services to Indonesian Migrant Workers through the BPJS Ketenagakerjaan Death Security. The heirs will receive cash benefits if Indonesian migrant worker dies. However, in practice, each BPJS Ketenagakerjaan branch office has its own regulations regarding the procedure for claiming death benefits. In this case, the BPJS Ketenagakerjaan Branch of Karimun Jawa in East Java provides file requirements that differ from the Regulation of the Minister of Manpower and Transmigration Number 18 of 2018 concerning Social Security for Indonesian Migrant Workers, which impedes the heirs. Furthermore, the level of education and family members of the Indonesian migrant workers from small towns prevent them from learning about the Death Insurance Claim procedure at BPJS Ketenagakerjaan Karimun Jawa.